Kepemimpinan Transformasional di Pondok Pesantren - Bambang Wahrudin; Binti Maunah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
Islamic educational institutions that want to progress require superior leadership. For this reason, the development of leadership models for Islamic educational institutions needs to continue to be developed. Many Islamic educational institutions are unable to develop and experience setbacks due to weak leadership. Therefore, various models of Islamic leadership need to be realized as an advantage for Islamic educational institutions. One of the leadership models that is currently developing is transformational leadership, which is one of the leadership models that has succeeded in bringing Islamic educational institutions to excellence. Transformational leadership cannot be separated from the institutional environment and superior human resources so that they are able to apply the transformational model in the management of Islamic educational institutions. Therefore, it is important for the development of Islam to know the characteristics of transformational leadership. Through the qualitative research method of this literature study, the researcher used references from various data sources and then processed them in depth to find the characteristics of transformational leadership in Islam. From this research, the results showed that the characteristics of transformational leadership in Islamic educational institutions include: 1) Idealized Influence, 2) Inspirational Motivation, 3) Intellectual Stimulation, and 4) Individualized Consideration. ). Islamic educational institutions that have a transformational leadership character are institutions that have excellence and good quality educational services as well as a superior work culture.